Lead Phytochemicals for Anticancer Drug Development - Singh, Sukhdev; Sharma, Bhupender; Kanwar, Shamsher S.; Kumar, Ashok (Frontiers in Plant Science, 2016)
Cancer is a serious concern at present. A large number of patients die each year due to cancer illnesses in spite of several interventions available. Development of an effective and side effects lacking anticancer therapy is the trending research direction in healthcare pharmacy. Chemical entities present in plants proved to be very potential in this regard. Bioactive phytochemicals are preferential as they pretend differentially on cancer cells only, without altering normal cells. Carcinogenesis is a complex process and includes multiple signaling events. Phytochemicals are pleiotropic in their function and target these events in multiple manners; hence they are most suitable candidate for anticancer drug development. Efforts are in progress to develop lead candidates from phytochemicals those can block or retard the growth of cancer without any side effect. Several phytochemicals manifest anticancer function in vitro and in vivo. This article deals with these lead phytomolecules with their action mechanisms on nuclear and cellular factors involved in carcinogenesis. Additionally, druggability parameters and clinical development of anticancer phytomolecules have also been discussed.